Dimsum Ichi's MSME Digital Marketing Communication Strategy in Increasing Product Sales - Aji Azhanuddin Pratito; Komarudin; Badarudin Azarkasyi (Universitas Muhammadiyah Palu, 2026)
This research aims to find out the form of strategy and effectiveness of digital marketing communication applied by Dimsum Ichi MSMEs in marketing their products to consumers. The problem contained in this study is that the implementation of digital marketing communication strategies carried out is not clearly known, especially in terms of planning, management, and effectiveness in increasing product sales. The type of research used is field research with a qualitative approach that is descriptive. The data collection methodology used in this study is observation, documentation and interviews. The primary data sources in this study are the Owners/Managers of Dimsum Ichi MSMEs, Dimsum Ichi Digital Media Activities, and active consumers, while secondary data sources are obtained from documentation obtained from the results of the research. The technique for analyzing data is through three stages, namely: 1) data reduction, 2) data presentation, and 3) drawing conclusions or verification. Based on the results of the research, the digital marketing communication strategies implemented are not only effective in increasing sales, but are also supported by other interrelated supporting factors in driving the success of product marketing.